INFLUENCE OF HETEROVALENT SUBSTITUTION ON THE CONDUCTIVITY OF MxPb1-xSnF4±х AND MxPb0,86-xSn1,14F4±х (M=K, Rb, Nd, Sm) FLUORIDE-CONDUCTING PHASES - Nahornyi, Anton; Omelchuk, Anatolii (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2025)
In this article was evaluated effect of partial substitution of lead cations with K+, Rb+, Nd3+, Sm3+ cations on the conductivity of the synthesized fluoride-conducting phases MxPb1-xSnF4±x and MxPb0.86-xSn1.14F4±x. The non-stoichiometric phase Pb0.86Sn1.14F4 is characterized by high conductivity, which at 373 K is 2.9∙10-3 S/cm and is almost an order of magnitude higher than the conductivity of β-PbSnF4. In contrast to the stoichiometric β-PbSnF4 phase, the substitution of some lead cations with K+, Rb+, Nd3+, Sm3+ cations increases the electrical conductivity of said Pb0.86-xSn1.14F4 phase at both low and high temperatures. The phases formed by the partial substitution of lead cations by the said substituents with the highest conductivity values are as follows: K0.03Pb0.83Sn1.14F3.97 (σ373 = 0.12 S/cm, σ573 = 0.37 S/cm), Rb0.2Pb0.66Sn1.14F3.80 (σ373 = 7.72∙10-2 S/cm, σ573 = 0.34 S/cm), Pb0.69Nd0.17Sn1.14F4.17 (σ373 = 3.7∙10-2 S/cm, σ573 = 0.33 S/cm) and Pb0.76Sm0.10Sn1.14F4.10(σ373 = 1.1∙10-2 S/cm, σ573 = 0.12 S/cm). On the other hand substitution of some lead cations with K+, Rb+, Nd3+, Sm3+ cations increases the conductivity of the initial β-PbSnF4 phase only in the high temperature region. At 573 K, the best substituents are K+ (x = 0.10) and Sm3+ (x = 0.15) cations. The conductivity values of the K0.1Pb0.9SnF3.9 and Sm0.15Pb0.85SnF4.15 phases are 7.95∙10-2 and 7.97∙10-2 S/cm, respectively. At 373 K, only the Nd3+ (0.06 ≤ x ≤ 0.14) and Rb+ (0.03 ≤ x ≤ 0.06) cations contribute to the increase in electrical conductivity. The highest conductivity (4.8∙10-3 S/cm) is observed in the phase of Nd0.10Pb0.90SnF4.10composition. K+ and Sm3+ cations form phases with lower conductivity compared to the original β-PbSnF4 phase. Charge transfer in the synthesized phases according to the results of the evaluation of the electronic component of the conductivity by the Hebb – Wagner method is provided by fluoride anions.